Association Between Exclusive Breastfeeding and Maternal Knowledge of Toddler Nutrition with Wasting Incidence in Toddlers - Tirta, Insani Tiara; Zulaikha, Fatma; Asthiningsih, Ni Wayan Wiwin (Inspirasi Foundation, 2025)
Introduction: Wasting is an acute nutritional disorder in toddlers that can lead to impaired growth and increased morbidity. Exclusive breastfeeding and maternal knowledge about toddler nutrition are key factors influencing nutritional status. This study aims to examine the association between exclusive breastfeeding and maternal knowledge of nutrition with the incidence of wasting among toddlers in the working area of Sidomulyo Health Center, Samarinda City. Methods: This study employed a quantitative analytical method with a cross-sectional design. A total of 188 mothers and toddlers were sampled using stratified random sampling, and 168 toddlers met the inclusion criteria for analysis. Data were collected through structured questionnaires and anthropometric measurements. The Chi-Square test was used to analyze the association between variables, and odds ratios (OR) were calculated to determine risk levels. Results: Among the 168 toddlers, 43 (25.6%) were identified as experiencing wasting. A significant association was found between exclusive breastfeeding and wasting incidence (p = 0.000; OR = 0.111; 95% CI = 0.049–0.255), indicating that children who were not exclusively breastfed had a higher risk of wasting. Maternal knowledge of toddler nutrition also showed a significant relationship with wasting (p = 0.000), where poor maternal knowledge was associated with a higher incidence of wasting. Conclusion: Exclusive breastfeeding and good maternal knowledge about toddler nutrition are protective factors against wasting. Health promotion strategies at the community health center level should prioritize increasing awareness and education regarding exclusive breastfeeding and toddler nutritional needs to reduce the prevalence of wasting.